2012
DOI: 10.1186/1471-2164-13-46
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in SHSY5Y cells exposed to okadaic acid by suppression subtractive hybridization

Abstract: BackgroundOkadaic acid (OA), a toxin produced by several dinoflagellate species is responsible for frequent food poisonings associated to shellfish consumption. Although several studies have documented the OA effects on different processes such as cell transformation, apoptosis, DNA repair or embryogenesis, the molecular mechanistic basis for these and other effects is not completely understood and the number of controversial data on OA is increasing in the literature.ResultsIn this study, we used suppression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 105 publications
(119 reference statements)
2
14
0
Order By: Relevance
“…Also, a reduction of the levels of NPY in the intestine is directly related to the diarrheic episodes (Chandrasekharan et al, 2013). Our data supports a recent study that demonstrated the down-regulation of the NPY gene expression on the SH-SY5Y neuronal cell line (Valdiglesias et al, 2012). In vivo all those effects could produce diarrhea.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, a reduction of the levels of NPY in the intestine is directly related to the diarrheic episodes (Chandrasekharan et al, 2013). Our data supports a recent study that demonstrated the down-regulation of the NPY gene expression on the SH-SY5Y neuronal cell line (Valdiglesias et al, 2012). In vivo all those effects could produce diarrhea.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study OA and DTX1 reduced the viability of the neuronal SH-SY5Y cells being DTX1 4 to 5 times more potent than OA. Together with neuronal morphological alterations, OA was also found to modify the expression of genes related to cytoskeleton and neurotransmission in neuronal cells (Valdiglesias et al, 2012). We investigated the effects of OA on the levels of NPY in SH-SY5Y cells after 1, 6, 12 and 24 h treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a large number of studies contributed to better understand the influence of OA (Valdiglesias et al, 2012a(Valdiglesias et al, , 2012b, showing the role played in promoting apoptosis, cytoskeleton disruption, and cell cycle alterations in mammalian cell lines . Unfortunately, the assessment of OA-induced toxicity in marine organisms, which constitute an important economic and ecological relevance, is still limited .…”
Section: Early Effects Of Okadaic Acid In Mussels 815mentioning
confidence: 99%
“…Chin et al (2000) used differential display in human glioma model T89G cells to show OA-induced upregulation of transcription factors, oxidative metabolism proteins, phosphorylation substrates, and stress response genes after 2.5 hr exposures. Valdiglesias et al (2012) used subtractive hybridization in the human neuroblastoma cell line SHSY5Y to show OA induced up and down gene regulation depending on the time of exposure from 2–48 hr with the affected genes playing roles in translation, transcription, signal transduction, metabolism, cell cycle control and apoptosis, transport, and cytoskeletal processes. The study of OA-mediated concentration effects adds to these insights.…”
Section: Discussionmentioning
confidence: 99%